2013
DOI: 10.4236/jibtva.2013.24006
|View full text |Cite
|
Sign up to set email alerts
|

PKC Is a Target to Modulate the Expression of Receptor Mediated Endocytosis (RME) Mice Macrophages BALB/c for Optimizing the Phagocytosis toward Candida albicans

Abstract: Introduction: The existence of receptor-mediated endocytosis (RME) means that selectivity and selectivity occurs in capturing macromolecules. Protein kinase C (PKC) which can be expressed by almost all cells are proteins important in signal transduction groove that plays a role in a number of cell activity, e.g. phagocytosis. Aims: The purpose of this study is to determine the expression of RME after modulating the PKC which is characterized by the number of Candida albicans cells attached to the surface of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Recently, Oskoueian et al [9] reported that extract of root and latex of J. curcas plant which contained phenolics, flavonoid and saponins showed notable antioxidant, anticancer and anti-inflammatory activities. These compounds have been reported to be involved in the biological activities of the plants [10]. Ricinus communis is a same species of plant that can vary greatly in growth patterns and appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Oskoueian et al [9] reported that extract of root and latex of J. curcas plant which contained phenolics, flavonoid and saponins showed notable antioxidant, anticancer and anti-inflammatory activities. These compounds have been reported to be involved in the biological activities of the plants [10]. Ricinus communis is a same species of plant that can vary greatly in growth patterns and appearance.…”
Section: Discussionmentioning
confidence: 99%